Arthroscopy of the Elbow in Clinically Normal Dog Using the Caudal Portals - Bartlet, J.F. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
The technique of arthroscopy of the elbow joint using the caudal portals is described. It was developed on six cadavers and six experimental dogs and allows a direct visualization of the olecranon fossa, caudolateral, caudo-medial and cranial compartments of the elbow joint. Arthroscopy of the caudal aspect of the elbow joint appears safe and reliable. None of anatomical structures are at risk on the caudal aspect of the elbow joint.
Keywords: Arthroscopy; elbow; canine